Peringkas teks otomatis pada artikel berbahasa indonesia menggunakan metode maximum marginal relevance - Idhafi, Zaky; Agustian, Surya; Yanto, Febi; Safaat H, Nazruddin (Universitas Muhammadiyah Riau, 2023)
Automated text summarization is a method for retrieving the essence of one or more text documents. Automatic Text Summarizer is needed for a faster and more efficient process of reading, searching, and understanding information. This study proposes the Maximum Marginal Relevance method to carry out the text summarization process automatically. The method was developed and tested on each of the 150 Indonesian article documents. The summary is generated from the similarity score between sentences calculated using cosine similarity. MMR's performance in producing summaries was evaluated using ROUGE (Recall-Oriented Understudy for Gisting Evaluation), which compares them to gold-generated summaries. Test results for a compression rate of 50% gave F1 scores on ROUGE-1, ROUGE-2, and ROUGE-L at 71.86%, 64.18%, and 71.56%, respectively. In comparison, the test results with a compression rate of 30% produced F1-scores for ROUGE-1, ROUGE-2, and ROUGE-L, respectively 62.95%, 53.61%, and 62.47%. Compared to previous studies, this study produced better scores.